Modified TiO2 photocatalytic material as well as preparation method and application thereof
By modifying TiO2 to increase its specific surface area, the problem of low hydrogen production efficiency of TiO2 photocatalysts is solved, and the effect of significantly improving the hydrogen production performance and cycle stability of photocatalytic materials is achieved.
Patent Information
- Application Number
- CN202411865786.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-18
AI Technical Summary
As a photocatalyst, TiO2 has problems such as narrow light absorption range, high photogenerated carrier recombination rate, limited surface adsorption capacity, and low quantum yield, resulting in low hydrogen production efficiency.
By modifying TiO2 with metals Sn and Pt, the size of the photocatalytic material is reduced and the specific surface area is increased, thereby improving the hydrogen production performance of the photocatalytic material.
By modifying TiO2, the hydrogen production performance of the photocatalytic material is significantly improved, which greatly increases its hydrogen production, and the modified material performs well in the cycle stability test.
Smart Images

Figure CN119633815A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic materials, and in particular to a modified TiO2 photocatalytic material and a preparation method and application thereof. Background Art
[0002] With the development of the current society and the acceleration of industrialization, the problem of energy shortage has become increasingly prominent, seriously affecting human health and life. Solar energy is inexhaustible and easy to obtain. More and more researchers are committed to the development and application of semiconductor photocatalytic technology using solar energy. Producing hydrogen (H2) through photocatalytic water splitting is one of the most promising clean solar energy conversion technologies in recent decades. The ability of photocatalytic water splitting to produce energy means that we can use water as a fuel for future energy needs.
[0003] However, the production process of semiconductor photocatalysts is complex and the material cost is high, which restricts the commercial scale application of the technology. Among various photocatalytic materials, titanium dioxide (TiO2) has become the dominant and most widely studied material due to its unique physical and chemical properties. However, as a photocatalyst, TiO2 has problems such as narrow light absorption range, high recombination rate of photogenerated carriers, limited surface adsorption capacity, and low quantum yield, which leads to low hydrogen production efficiency.
[0004] It should be noted that the information disclosed in the above background technology section is only used to enhance the understanding of the background of the present disclosure, and therefore may include information that does not constitute the prior art known to ordinary technicians in the field. Summary of the invention
[0005] The technical task of the present application is to address the above deficiencies and provide a modified TiO2 photocatalytic material and its preparation method and application. The present application uses metal Sn and Pt to modify TiO2, which can reduce the size of the photocatalytic material and then increase the specific surface area of the photocatalytic material, thereby improving the hydrogen production performance of the photocatalytic material in practical applications.
[0006] To achieve the above objectives, this application provides the following technical solutions: According to one aspect of the present application, a modified TiO2 photocatalytic material is provided, comprising: a modified Sn / TiO2 photocatalytic material and metal Pt atoms doped in the modified Sn / TiO2 photocatalytic material.
[0007] In some embodiments, the modified Sn / TiO 2 photocatalytic material includes: TiO 2 and metal Sn atoms doped in the TiO 2 .
[0008] In some embodiments, the TiO2 is nanocrystalline, the metal Sn atoms are single atoms, and the metal Pt atoms are clusters.
[0009] In some embodiments, the doping amount of the metal Sn atoms in the modified TiO2 photocatalytic material is 1-3 wt %, and the doping amount of the metal Pt atoms in the modified TiO2 photocatalytic material is 0.5-2 wt %.
[0010] According to another aspect of the present application, a method for preparing a modified TiO2 photocatalytic material is also provided, comprising: adding tetrabutyl titanate to anhydrous ethanol and stirring to obtain a titanium source alcohol solution; adding stannous chloride and hydrochloric acid to deionized water and stirring to obtain a mixed aqueous solution; slowly dropping the titanium source alcohol solution into the mixed aqueous solution to obtain a Sn / TiO2 colloidal solution; aging the Sn / TiO2 colloidal solution to separate the solid from the liquid, washing and drying the solid after the solid-liquid separation to obtain a Sn / TiO2 powder; grinding the Sn / TiO2 powder, calcining it in a tubular furnace under an air atmosphere, and cooling it to room temperature to obtain a modified Sn / TiO2 photocatalytic material; and doping metal Pt atoms into the modified Sn / TiO2 photocatalytic material to obtain a modified Sn-Pt / TiO2 photocatalytic material.
[0011] In some embodiments, the process of doping the metal Pt atoms into the modified Sn / TiO2 photocatalytic material comprises: ultrasonically dispersing the modified Sn / TiO2 photocatalytic material in a mixed solution of deionized water and methanol, adding an aqueous solution of chloroplatinic acid thereto, and continuously stirring the solution under vacuum of Labsolar-6A and irradiation with a 300W xenon lamp to obtain a modified Sn-Pt / TiO2 photocatalytic material.
[0012] In some embodiments, the mass ratio of the tetrabutyl titanate to the anhydrous ethanol is 1:5; the stannous chloride is anhydrous stannous chloride, and the mass ratio of the anhydrous stannous chloride to the tetrabutyl titanate is 0.00375:1; the volume ratio of the anhydrous ethanol to the deionized water is 1:1; and the amount of hydrochloric acid added is 2 drops.
[0013] In some embodiments, the concentration of metal Pt atoms in the chloroplatinic acid aqueous solution is 1.5066 mg / mL; in the modified TiO2 photocatalytic material, the mass ratio of the metal Sn atoms to the Ti atoms is 100:1-3, and the mass ratio of the metal Pt atoms to the Ti atoms is 100:0.5-2.
[0014] In some embodiments, the aging time is 24 hours; the solid-liquid separation is centrifugal separation, wherein the rotation speed of the centrifugal separation is 10000-12000r / min, and the centrifugal time is 3-5min; the drying temperature is 80-100°C, and the drying time is 12h; the calcination temperature is 450-500°C, the calcination time is 2-3h, and the calcination heating rate is 3-5°C / min.
[0015] According to another aspect of the present application, there is also provided an application of a modified TiO2 photocatalytic material in photocatalytic hydrogen production.
[0016] Compared with the prior art, the advantages and positive effects of this application are: The present application uses metal Sn and Pt to modify TiO2, which can reduce the size of the photocatalytic material and then increase the specific surface area of the photocatalytic material, thereby improving the hydrogen production performance of the photocatalytic material in practical applications.
[0017] Furthermore, the present application selects different doping amounts to more accurately select the doping ratio of the photocatalyst, thereby further improving the hydrogen production performance of the photocatalytic material. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 A flow chart of a method for preparing a photocatalytic material in some embodiments of the present application is shown.
[0020] Figure 2 The X-ray diffraction patterns of the photocatalytic materials in Example 1 and Comparative Examples 1-2 of the present application are shown.
[0021] Figure 3 The transmission electron microscope images of the photocatalytic materials in Example 1 and Comparative Examples 1-2 of the present application are shown.
[0022] Figure 4 TEM images of the photocatalytic materials in Example 1 and Comparative Example 1 of the present application are shown.
[0023] Figure 5 The mapping distribution diagram of the photocatalytic material prepared in Example 1 of the present application is shown.
[0024] Figure 6 The photocurrent curves of the photocatalytic materials prepared in Example 1 and Comparative Examples 1-2 of the present application are shown.
[0025] Figure 7 The linear sweep voltammetry curves of the photocatalytic materials prepared in Example 1 and Comparative Examples 1-2 of the present application are shown.
[0026] Figure 8 The electrochemical impedance spectrum curves of the photocatalytic materials prepared in Example 1 and Comparative Examples 1-2 of the present application are shown.
[0027] Fig. 9 The Ti 2p X-ray photoelectron spectra of the photocatalytic materials prepared in Example 1 and Comparative Examples 1-3 of the present application are shown.
[0028] Fig.10 The Pt 4f X-ray photoelectron spectra of the photocatalytic materials prepared in Example 1 and Comparative Example 2 of the present application are shown.
[0029] Fig.11 The hydrogen production performance diagram of the photocatalytic materials in Examples 1-3 and Comparative Examples 1-2 of the present application is shown.
[0030] Fig.12 The hydrogen production performance diagram of the photocatalytic material in Examples 1, 4-6 of the present application is shown.
[0031] Fig.13 The graph shows the test results of the cyclic stability of the photocatalytic material in Example 1 of the present application. DETAILED DESCRIPTION
[0032] In order to more clearly understand the above-mentioned purposes, features and advantages of the present application, the present application is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0033] The present application is further described below in conjunction with the accompanying drawings and specific embodiments.
[0034] Example 1 Please refer to the attached Figure 1 , a method for preparing a photocatalytic material, comprising the following steps: S1. Add 40 mL of anhydrous ethanol into a clean beaker, then add 8 mL of tetrabutyl titanate (TBOT), and stir vigorously for 30 min to obtain a titanium source alcohol solution.
[0035] S2. Add 30 mg of anhydrous stannous chloride, 2 drops of hydrochloric acid and 40 mL of deionized water into another clean beaker and perform sonication in an ultrasonic machine to obtain a mixed aqueous solution.
[0036] S3. Add the titanium source alcohol solution dropwise into the mixed aqueous solution, and stir vigorously and rapidly for 30 minutes to obtain a Sn / TiO2 colloidal solution.
[0037] S4. Place the Sn / TiO2 colloidal solution under light-shielding conditions, age it for 24 hours, then centrifuge dry it, wash the solution with deionized water and ethanol, wash it three times respectively, and then dry it in an oven at 100°C.
[0038] S5. After drying, the material obtained in S4 is ground in a mortar and calcined in a tubular furnace under an air atmosphere at 450°C for 2h with a heating rate of 5°C / min. After cooling to room temperature, a modified Sn / TiO2 photocatalytic material is obtained.
[0039] S6. Disperse 10 mg of the modified Sn / TiO2 photocatalytic material powder obtained in step S5 in a mixed solution of 45 mL of deionized water and 5 mL of methanol, ultrasonically disperse the catalyst, add 67 μL of chloroplatinic acid aqueous solution to the solution, place the reactor in a Labsolar-6A for vacuum to remove dissolved oxygen in the solution, control the entire reaction temperature at 10°C by condensing water, continue stirring, and place it under a 300 W xenon lamp for irradiation for 30 minutes to obtain 1.0 wt% Sn-1.0 wt% Pt / TiO2 photocatalytic material.
[0040] Example 2 Compared with the method in Example 1, the difference is that the amount of anhydrous stannous chloride added to S2 is 60 mg, and the other steps are the same as in Example 1 and will not be repeated here to obtain 2.0wt%Sn-1.0wt%Pt / TiO2 photocatalytic material.
[0041] Example 3 Compared with the method in Example 1, the difference is that the amount of anhydrous stannous chloride added to S2 is 90 mg, and the other steps are the same as in Example 1 and will not be repeated here to obtain 3.0wt%Sn-1.0wt%Pt / TiO2 photocatalytic material.
[0042] Example 4 Compared with the method in Example 1, the difference is that the amount of chloroplatinic acid aqueous solution added in S4 is 34 μL, and the other steps are the same as in Example 1 and will not be repeated here to obtain 1.0 wt% Sn-0.5 wt% Pt / TiO2 photocatalytic material.
[0043] Example 5 Compared with the method in Example 1, the difference is that the amount of chloroplatinic acid aqueous solution added in S4 is 101 μL, and the other steps are the same as in Example 1 and will not be repeated here to obtain 1.0wt% Sn-1.5wt% Pt / TiO2 photocatalytic material.
[0044] Example 6 Compared with the method in Example 1, the difference is that the amount of chloroplatinic acid aqueous solution added in S4 is 134 μL, and the other steps are the same as in Example 1 and will not be repeated here to obtain 1.0 wt% Sn-2.0 wt% Pt / TiO2 photocatalytic material.
[0045] Comparative Example 1: The TiO2 photocatalytic material was prepared according to steps S1-S5 in Example 1. The difference from steps S1-S5 in Example 1 is that anhydrous tin chloride is not added in S2. The other steps are the same as S1-S5 in Example 1 and will not be repeated here.
[0046] Comparative Example 2: The preparation was carried out according to the steps of Example 1, the difference from the steps of Example 1 being that anhydrous tin chloride was not added to S2, and the other steps were the same as those of Example 1 and will not be repeated here, to obtain a Pt / TiO2 photocatalytic material.
[0047] Comparative Example 3: The Sn / TiO2 photocatalytic material was prepared according to the steps of Example 1, the difference from the steps of Example 1 being that S6 was not included, and the other steps were the same as those of Example 1 and will not be repeated here, to obtain the Sn / TiO2 photocatalytic material.
[0048] The photocatalytic materials prepared in Example 1 and Comparative Examples 1-2 were subjected to X-ray diffraction. The results are shown in detail in Figure 2 . Figure 2 The XRD patterns of TiO2 photocatalyst material, 1.0wt%Pt / TiO2 photocatalyst material and 1.0wt%Sn-1.0wt%Pt / SnO2 photocatalyst material are shown. Figure 2 As shown, the prepared photocatalytic material has obvious diffraction peaks at diffraction angles of 25.281°, 37.8°, 48.049°, 53.89°, 55.06°, 62.688°, and 75.029°, corresponding to the (101), (004), (200), (105), (211), (204), and (215) crystal planes of TiO2 (PDF#21-1272), respectively. It is observed in the figure that the diffraction peak intensities at low angles are different, and the peak positions are shifted, which is caused by the doping of Sn and Pt metals.
[0049] The photocatalytic materials prepared in Example 1 and Comparative Examples 1-2 were observed using a transmission electron microscope. Figure 3 ,in, Figure 3 a is a scanning electron microscope photo of the TiO2 photocatalytic material prepared in Comparative Example 1, Figure 3 b is a scanning electron microscope photo of the 1.0wt% Pt / TiO2 photocatalytic material prepared in Comparative Example 2, Figure 3c is a scanning electron microscope photo of the 1.0wt% Sn-1.0wt% Pt / TiO2 photocatalytic material prepared in Example 1. Figure 3 As shown, the TiO2 photocatalytic material prepared in the comparative example is nanocrystalline. After being doped with metal Pt and Sn, the Pt / TiO2 and Sn-Pt / TiO2 photocatalytic materials maintain the nanocrystalline state. The size of the photocatalytic material is reduced and the specific surface area is increased, which is more conducive to the reaction of the photocatalytic material, thereby enhancing its hydrogen production performance.
[0050] Figure 4 TEM images of the photocatalytic materials prepared in Example 1 and Comparative Example 1 of the present application are shown, wherein 4a is Comparative Example 1 and 4b is Example 1. Figure 4 It can be seen that comparative example 1 has obvious lattice fringes TiO2 (101) d = 0.351nm, and after doping TiO2 (101) d = 0.354nm. Figure 5 The mapping distribution diagram of the photocatalytic material prepared in Example 1 is shown. Figure 5 It can be seen that in the photocatalytic material prepared in Example 1, O, Ti and Sn are evenly distributed, and the Pt particles are bright spots in the figure.
[0051] Figure 6-8 The photocurrent curve, linear sweep voltammetry curve, and electrochemical impedance spectroscopy curve of the photocatalytic materials prepared in Example 1 and Comparative Examples 1-2 of the present application are shown respectively. Figure 6-8 It can be seen that the larger the transient photocurrent, the more efficient the separation of photogenerated electrons and holes and the stronger the charge transfer efficiency. The current-time (IT) curve shows that under the joint action of Pt and Sn, the photocurrent intensity is greatly increased, which indicates that a large number of photogenerated carriers are generated during the illumination process, and the photocatalytic activity of the composite material is significantly improved. The linear sweep voltammetry (LSV) curve shows that at the same current density, the overpotential of Pt-Sn-TiO2 is the smallest. The electrochemical impedance spectroscopy (EIS) curve shows that the arc radius of the Pt-Sn-TiO2 composite material is small, indicating that the composite material has a strong ability to conduct photogenerated carriers, which is consistent with the photocurrent results.
[0052] Fig. 9 The Ti 2p X-ray photoelectron spectra of the photocatalytic materials prepared in Example 1 and Comparative Examples 1-3 of the present application are shown. Fig.10 The Pt 4f X-ray photoelectron spectrum of the photocatalytic materials prepared in Example 1 and Comparative Example 2 of the present application is shown. Figure 9-10It can be seen that the addition of Sn will change the electronic structure of TiO2. The electronegativity of Sn is different from that of Ti. When Sn enters the TiO2 lattice, it will cause the electron cloud density to be redistributed, and electrons will transfer from Ti to Sn to a certain extent, thereby increasing the electron cloud density around Ti and reducing the binding energy of Ti. There is a strong interaction between Pt and TiO2, which will cause electrons to transfer from TiO2 to Pt, reducing the electron cloud density around Ti and reducing the binding energy of Ti. The addition of Sn and Pt may trigger the transfer of electrons from Sn to Pt, resulting in an increase in the binding energy of Pt.
[0053] The test results of the hydrogen production performance of the photocatalytic materials of Examples 1-3 and Comparative Examples 1-2 are detailed in Fig.11 The test results of hydrogen production performance of the photocatalytic materials of Examples 1 and 4-6 are detailed in Fig.12 .
[0054] The test method is as follows: The photocatalytic hydrogen production experiment was carried out in a 100mL quartz reactor. The temperature of the circulating condensed water was 4°C. A 300W xenon lamp was used as the UV-visible light source. In a typical experiment, 10mg of sample was placed in 50mL of a mixed solvent (water / methanol) with a volume ratio of 9:1 in a quartz reactor. The quartz reactor was thoroughly degassed, evacuated for 30min, and backfilled with pure Ar2 three times. The reaction was carried out in a Labsolar-6A all-glass automatic online trace gas analysis system.
[0055] Depend on Fig.11 It can be seen that 1.0wt% Sn-1.0wt% Pt / TiO2 photocatalyst material has the best hydrogen production performance compared with TiO2 photocatalyst material, which is 202.2 times the hydrogen production of TiO2 photocatalyst material and twice the hydrogen production of 1.0wt% Pt / TiO2 photocatalyst material.
[0056] Depend on Fig.12 It can be seen that in comparing the photocatalytic hydrogen production performance of Example 1 and Examples 4-6, it can be found that Example 1, that is, 1.0wt%Sn-1.0wt%Pt / TiO2 photocatalytic material, has the highest photocatalytic hydrogen production performance.
[0057] See also Fig.13 , a cyclic stability test was conducted on 1.0wt%Sn-1.0wt%Pt / TiO2 photocatalytic material to investigate the repeatability and stability performance of the photocatalytic material. Fig.13 It can be seen that after 4 cycles, the 1.0wt% Sn-1.0wt% Pt / TiO2 photocatalytic material has good repeatability and stability.
[0058] Through the above specific implementations, those skilled in the art can easily implement the present application. However, it should be understood that the present application is not limited to the above specific implementations. Based on the disclosed implementations, those skilled in the art can arbitrarily combine different technical features to achieve different technical solutions.
Claims
1. A modified TiO2 photocatalytic material, characterized in that: include: A modified Sn / TiO2 photocatalytic material and metal Pt atoms doped in the modified Sn / TiO2 photocatalytic material.
2. A modified TiO2 photocatalytic material according to claim 1, characterized in that: The modified Sn / TiO2 photocatalytic material comprises: TiO2 and metal Sn atoms doped in the TiO2.
3. A modified TiO2 photocatalytic material according to claim 2, characterized in that: The TiO2 is nanocrystalline, the metal Sn atoms are single atoms, and the metal Pt atoms are clusters.
4. A modified TiO2 photocatalytic material according to claim 2, characterized in that: The doping amount of the metal Sn atoms in the modified TiO2 photocatalytic material is 1-3 wt %, and the doping amount of the metal Pt atoms in the modified TiO2 photocatalytic material is 0.5-2 wt %.
5. The method for preparing a modified TiO2 photocatalytic material according to claim 1, characterized in that: include: Tetrabutyl titanate is added into anhydrous ethanol and stirred to obtain a titanium source alcohol solution; Add stannous chloride and hydrochloric acid into deionized water and stir to obtain a mixed aqueous solution; Slowly adding the titanium source alcohol solution dropwise to the mixed aqueous solution to obtain a Sn / TiO2 colloidal solution; Aging the Sn / TiO2 colloidal solution to separate the solid from the liquid, washing and drying the solid after the solid-liquid separation to obtain Sn / TiO2 powder; Grinding the Sn / TiO2 powder, calcining it in a tube furnace under air atmosphere, and cooling it to room temperature to obtain a modified Sn / TiO2 photocatalytic material; The metal Pt atoms are doped into the modified Sn / TiO2 photocatalytic material to obtain the modified Sn-Pt / TiO2 photocatalytic material.
6. The method for preparing a modified TiO2 photocatalytic material according to claim 5, characterized in that: The step of doping metal Pt atoms into the modified Sn / TiO2 photocatalytic material comprises: The modified Sn / TiO2 photocatalytic material was ultrasonically dispersed in a mixed solution of deionized water and methanol, and then an aqueous solution of chloroplatinic acid was added thereto. The mixture was continuously stirred under vacuum state of Labsolar-6A and irradiation of a 300W xenon lamp to obtain a modified Sn-Pt / TiO2 photocatalytic material.
7. The method for preparing a modified TiO2 photocatalytic material according to claim 5, characterized in that: The mass ratio of the tetrabutyl titanate to the anhydrous ethanol is 1:5; the stannous chloride is anhydrous stannous chloride, and the mass ratio of the anhydrous stannous chloride to the tetrabutyl titanate is 0.00375:1; the volume ratio of the anhydrous ethanol to the deionized water is 1:1; and the amount of hydrochloric acid added is 2 drops.
8. The method for preparing a modified TiO2 photocatalytic material according to claim 6, characterized in that: The concentration of metal Pt atoms in the chloroplatinic acid aqueous solution is 1.5066 mg / mL; in the modified TiO2 photocatalytic material, the mass ratio of the metal Sn atoms to the Ti atoms is 100:1-3, and the mass ratio of the metal Pt atoms to the Ti atoms is 100:0.5-2.
9. The method for preparing a modified TiO2 photocatalytic material according to claim 5, characterized in that: The aging time is 24 hours; the solid-liquid separation is centrifugal separation, wherein the rotation speed of the centrifugal separation is 10000-12000r / min, and the centrifugal time is 3-5min; the drying temperature is 80-100°C, and the drying time is 12h; the calcination temperature is 450-500°C, the calcination time is 2-3h, and the calcination heating rate is 3-5°C / min.
10. Use of a modified TiO2 photocatalytic material according to any one of claims 1 to 9 in photocatalytic hydrogen production.